Dampak Social Commerce Pada Perilaku Impulse Buying Generasi Z - Eri Yanti Nasution; Tika Indria; Hastina Febriaty (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Online business in Indonesia has increased every year. This increase makes sellers continue to innovate in promotion and sales. One way that sellers do this is by utilizing social media as a means of selling products known as social commerce. Social commerce directly invites and makes consumers make purchases. This study aims to examine the impact of social commerce on impulse buying behavior of generation Z. The method of data collection is by distributing online questionnaires to 51 respondents of generation Z. This study uses simple regression analysis to see the impact of social commerce on impulse buying behavior. Based on the simple regression test and t test, it is concluded that social commerce has an impact on the impulse buying behavior of generation Z.